A 3D porous carbon foam loaded with Fe3O4/graphene oxide for highly effective As(iii) removal. (17th July 2020) - Ge, Xiao; Xie, Donghua; Zhang, Yunxia
Abstract : The Fe3 O4 /GO–CF monolith shows excellent removal performance toward As(iii ) due to efficient mass/ion transport pathways and abundant adsorption sites. Abstract : A 3D porous carbon foam (CF) loaded with Fe3 O4 /graphene oxide (GO) has been successfully fabricated. As expected, the saturated adsorption capacity of the resulting Fe3 O4 /GO–CF composite toward As(iii ) can reach up to 111 mg g −1, superior to those of most of the reported Fe-containing adsorbents. Additionally, the obtained Fe3 O4 /GO–CF exhibits excellent As(iii ) removal performance after five absorption–regeneration cycles with more than 70% of removal efficiency. The exceptional arsenic removal performance can be ascribed to its unique 3D porous network structure as well as fully exposed sorption sites originating from Fe3 O4 particles. Finally, the macroscopic size and magnetic feature of the Fe3 O4 /GO–CF monolith are favorable for facile separation after adsorption. Therefore, the hierarchically porous Fe3 O4 /GO–CF monolith is highly expected to find many potential applications in arsenic-contaminated water remediation.